Interpretation of the Bedawang Nala ornament located on the base of Pura Pabean in Buleleng Regency Indonesia - Made Mariada Rijasa; Ida Bagus Idedhyana (ARTEKS : Jurnal Teknik Arsitektur, 2022)
Pura (temple) is a sacred place for the Hindus in Bali, such as Pura Pabean, which is included in pura kahyangan jagat (temple for all people). Pura Pabean is located on the northern part of the main Singaraja-Gilimanuk road, Banyupoh Village, Gerokgak Sub-district, Buleleng Regency, Indonesia. The area also extends into the ocean and is positioned on steep rocky terrain. Unlike other Pura in Bali, this temple stands on the base of an ornament, as a Bedawang Nala (cosmic tortoise) with two dragons (serpents) wrapped around the body. The embodiments of the tortoise and the two dragons are the essential parts of the temple, with their heads overlooking the ocean. Therefore, this study aims to examine the interpretation of Bedawang Nala, as the Hindu icon located on the base of Pura Pabean. In this analysis, Capon's theory was developed and combined with the stages of the hermeneutic method. The analyzed Bedawang Nala was also a combination of Akupara (tortoise) with Vedava-nala (cosmic fire/fire of the apocalypse). This indicated that the body was similar to that of a tortoise, with the head being observed as a cosmic fire resembling the figure of a mare. The results showed that Bedawang functioned as an aesthetic and symbolic ornament, which depicted the bhu mandala (earth or region) in the middle of the ocean. This was a description of God's position in His manifestation, as the ruler of ports, trade, and water flow. These results are expected to develop the traditional Balinese architecture in the present and future activities and performances.